Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If A+B+C = 2S SinS + Sin(S-A) + Sin(S-B)-sin(S-c)=?

If A+B+C = 2S 
SinS + Sin(S-A) + Sin(S-B)-sin(S-c)=?

Grade:11

1 Answers

Rinkoo Gupta
askIITians Faculty 80 Points
7 years ago
sinS+sin(S-A)+sin(S-B)-sin(S-C)
{sinS-sin(S-C)}+{sin(S-A)+sin(S-B)}
2cos(2S-C)/2sin(C/2)+2sin(C/2)cos(B-A)/2
=2sinC/2[cos(A+B)/2 +cos(B-A)/2]
=2sinC/2 .[2cos(B/2)cos(A/2)]
=4cos(A/2)cos(B/2)sin(C/2)
Thanks & Regards
Rinkoo Gupta
askIITians Faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free